Estratégia de redução de danos em um Centro de Atenção Psicossocial Álcool e Drogas no município de Fortaleza: concepções e práticas - Lima, Raquel Cerdeira de (2019)
This research aims to understand concepts and practices of harm reduction (HR) strategy from the perspective of health professionals and Psychosocial Care Center for Alcohol and Drugs (PSCC AD) managers in Fortaleza, as a way to reflect on the role of HR in the care of alcohol and drugs users in the municipal Psychosocial Care Network (PSCN), guided by the regulatory frameworks of psychosocial care and drug policies, considering the political-ideological contradictions among them. It is a qualitative study, which dialogues with the field of public policy assessment, formed by theoretical and methodological assumptions that blended aspects of hermeneutic analysis and narrative analysis to construct results. Thirteen semi-structured interviews were conducted with health professionals and managers of a PSCC AD, with systematic observation of practices, and search and analysis of management documents between October 2018 and February 2019. HR concepts emerged in two main components: HR understood as a technique; HR understood as health care technology. The practices were generally understood as HR practices, although some professionals did not realize the use of the strategy in their own activities, recognizing it among the practices of colleagues. Furthermore, the user embracement apparatus was seen as a HR enhancer, and the daily work of this institution demonstrated the effectiveness of the strategy for the care of people who use drugs, highlighting the significance of formation moments and permanent education for the strategy adoption. In addition, the “Harm Reduction Group”, being a collaborative learning space among professionals, users and family members about HR, proved to be powerful for the consolidation of the strategy in this PSCC AD. Health professionals pointed out daily challenges for the operationalization and consolidation of HR in PSCN: difficulties in physical space, management and work processes, as well as fragile employment bonds that demotivate health workers and managers. The absence of management documents related to HR at the state, municipal and local levels has left us a gap in understanding these challenges. Finally, although professionals understand, value and practice HR in the surveyed institution, the toughening of drug policies in 2019 leaves numerous questions about the future of the strategy for the psychosocial care of alcohol and drug users.